University of Botswana Law Journal Volume 17, December 2013 (Pretoria University Law Press (PULP), 2014)
ARTICLES Nationality as an essential ingredient of diplomatic protection: Article 9 of the International Law Commission Draft Articles considered Amos O. Enabulele and Anthony Osaro Ewere Who is a tribesman? An examination of the continued utility of Section 3 of Botswana's Administration of Estates Act E Macharia-Mokobi Balancing contending interests: A focus on tax harmonisation and associated policy issues Aniyie I. Azuka NOTES Electoral democracy in Africa: A critique of jealousy Mbizvo Mawarire v Robert Gabriel Mugabe N.O. and 4 Others CCZ 1/13 Gift Manyatera and Chengetai Hamadziripi The abolition of the doctrine of immutability in the matrimonial property regime in Botswana Tebogo Jobeta and Obonye Jonas